General concepts of copyright and objects of copyright on the Internet. - Shermatov Nuriddin (Genius Publishing Group, 2023)
This theme delves into the fundamental principles of copyright and explores how these principles manifest in the dynamic landscape of the internet. The work provides a comprehensive overview of copyright, emphasizing its role in protecting creative works and fostering innovation. It also delves into the unique challenges and opportunities that arise in the digital age, highlighting the diverse objects of copyright found on the internet. The theme underscores the importance of understanding copyright in the context of the internet, where it serves as a cornerstone for balancing the rights of creators with the accessibility of information. Readers will gain a deeper insight into how copyright concepts shape the digital frontier, ensuring that the rights of creators are upheld while enabling the free exchange of ideas, culture, and knowledge on the web
Keywords: Copyright; intellectual property; fair use; digital rights